NURSES’ PERCEIVED FAMILIARITY WITH DISASTER PREPAREDNESS - Ng , X.J.; Lim , B.C.; Y, Azlina; Soon , Lean Keng (2016)
A major disaster, either natural or man-made, resulting in a large number of deaths and casualties, is hard to predict. Hence, preparing for, and responding to, a disaster is a public health priority that must be addressed, often in situations with constrained resources. The aim of this study was to assess nurses’ familiarity with disaster preparedness. A cross-sectional design was used. One hundred and thirty nurses were recruited using simple random sampling. Data was collected between December 2013 and February 2014 using a self-administered questionnaire. Pearson Chi Square analyses were used to determine the association between socio-demographic data and nurses’ perceived familiarity with disaster preparedness. A p value of ≤ 0.05 was considered statistically significant. The majority of the nurses were female (80%). Less than half were from the intensive care unit (30%). More than half were unfamiliar with disaster preparedness (62.3%). Among the socio-demographic factors, nurses’ workplace area was associated with perceived disaster preparedness [